2018
DOI: 10.1016/j.stemcr.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Translational Control of Sox9 RNA by mTORC1 Contributes to Skeletogenesis

Abstract: SummaryThe mechanistic/mammalian target of rapamycin complex 1 (mTORC1) regulates cellular function in various cell types. Although the role of mTORC1 in skeletogenesis has been investigated previously, here we show a critical role of mTORC1/4E-BPs/SOX9 axis in regulating skeletogenesis through its expression in undifferentiated mesenchymal cells. Inactivation of Raptor, a component of mTORC1, in limb buds before mesenchymal condensations resulted in a marked loss of both cartilage and bone. Mechanistically, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Importantly, GSEA analysis showed that hESC-sEVs treatment significantly activated the expression of genes involved in antiaging, stem cell proliferation and osteogenic differentiation. Among these genes, Sox9, Wnt4, Wnt10b, Wnt2b, Wnt6, and Fzd9 are associated with the Wnt signalling pathway and have been reported to enhance self-renewal and differentiation of MSCs as well as prevent skeletal ageing [ 37 39 , 49 , 50 ]. Pfkfb3, Nos and Cpt1b are Sirtuin signalling-related genes that have been demonstrated to promote cell cycle progression, suppress apoptosis, inhibit cellular ageing and stimulate bone regeneration [ 51 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, GSEA analysis showed that hESC-sEVs treatment significantly activated the expression of genes involved in antiaging, stem cell proliferation and osteogenic differentiation. Among these genes, Sox9, Wnt4, Wnt10b, Wnt2b, Wnt6, and Fzd9 are associated with the Wnt signalling pathway and have been reported to enhance self-renewal and differentiation of MSCs as well as prevent skeletal ageing [ 37 39 , 49 , 50 ]. Pfkfb3, Nos and Cpt1b are Sirtuin signalling-related genes that have been demonstrated to promote cell cycle progression, suppress apoptosis, inhibit cellular ageing and stimulate bone regeneration [ 51 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, Adamts5 and Mmp13 are crucial effectors of OA cartilage destruction and Col2a1 is crucial for the composition of hyaline ECM 21,32 . Rheb is located upstream of mTORC1 16,17 ; which is known to regulate cartilage formation via Sox 9 expression during mesenchymal condensation 33 In a study by Zhang et al, mTORC1 inhibition by Rheb deletion was shown to enhance collagenase-induced osteoarthritis by M2macrophages polarization in mice 34 . In contrary, some studies reported that mTOR is a positive regulator of OA and mTOR ablation protects cartilage and progression of OA 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Retroviral vectors were transfected into PLAT‐E cells using the calcium carbonate method. Virus supernatants were collected 48 h after transfection, and the cells were subsequently infected with virus supernatants for 24 h in the presence of 4 μg·mL −1 polybrene .…”
Section: Methodsmentioning
confidence: 99%